Sejarah Pergumulan Hukum Islam dan Budaya serta Implikasinya bagi Pembangunan Hukum Islam Khas Indonesia - Najitama, Fikria (Islamic University of Indonesia, 2007)
Historically, Islam law and the local culture do not always conflict each other. The local culture has a particular place in formulating Islamic law. This proves in adopting process of local culture of pra Islamic society either Prophetera or the generation after him, for instance era of companion and the founder of Islamic law school. In this sense, Imam Syafiâi has diffrencesopinion qaul qadim (old opinion of law) and qaul jadid (new opinion of law). This phenomenon describes the flexibility of Islamic law faces local cultures. Based on this, it need a new paradigm to Syariâah enforcement in Indonesia in term of how to implement Syariâah in Indonesia without abrogating the local culture. Kata kunci: hukum Islam, budaya, âurf, hukum Islam khas Indonesia.